Pengaruh Electronic Word Of Mouth, Social Media Advertising dan Citra Destinasi Terhadap Minat Berkunjung ke Wisata Hiu Paus Desa Labuhan Jambu di Kabupaten Sumbawa - Asrianti, Yuyun; Sulhaini, Sulhaini (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This research aims to determine the influence of electronic word of mouth, social media advertising, and destination image on interest in visiting whale shark tourism in Labuhan Jambu Village in Sumbawa Regency. The population in this study are all local tourists or domestic tourists who have an interest and local tourists who love marine tourism. The sample in this study consisted of 100 respondents. The sampling technique in this research used a nonprobability sampling technique with a purposive sampling method. Data analysis in this research used descriptive analysis and structural equation modelling (SEM). All research data was processed using SmartPLS 4. The research results showed that the indicators in the research carried out were declared valid and reliable. The results of this research also show that the three independent variables, namely electronic word of mouth, social media advertising, and destination image have a positive and significant effect on the dependent variable, namely interest in visiting.